Visual Modeling: “Unlocking Ideas and Enhancing Understanding: The Power of Visual Modeling” - Saloni Kumari (International Journal of Engineering and Technology, 2023)
To make ideas, concepts, or systems easier to comprehend and explain, visual modelling is the act of putting them into visual form. A range of methods and tools, including mind maps, flowcharts, diagrams, and wireframes, can be used to do this. In a range of settings, including business, education, and software development, visual models can be used to organize and clarify information, uncover links and patterns, and improve communication and teamwork. This paper discusses the SWOT analysis, the concept of use cases, the organization chart and its tiers, the stakeholder map, the scoring matrix, process flowcharts, and user stories.